FATTY ACID CONTENT IN DURIAN (Durio zibethinus, Murr) SEED - Eni SR; Sumarno . (Indonesian Journal of Pharmacy, 2001)
Fatty acids are part of fatty oils found in plants, animals and other organisms. Fatty oils are useful for human being, and they are also used as drug solvents, soaps, cosmetics and paint. Plant seeds usually contain fatty oil, protein and carbohydrate, useful for plants growth Durian seeds were just as common rubbish, therefore an investigation of fatty acids found in durian seeds were might be beneficial. Durian seeds were collected, dried, powdered, and was extracted with petroleum ether using Soxhlet apparatus. Physical and chemical parameters of Fatty oil i.e colour, acid value, saponification value, iodine value, and peroxide value were determined. Methyl ester of fatty acid composition produced by fatty oil transesterification was analyzed using a gas chromatography. The chemical parametrs of fatty oil are found to be: acid value (19,4 ± 0,17 ), saponification value (190,65 ± 0,84) , iodinevalue (81,7 ± 0,53) , and peroxide value (3,93 ± 0,12). Physical properties of fatty oil were : concentration of fatty oil was 6,12 ± 0,16 (%), w/w of dried seeds; transparenty yellow and durian odoured, the water content of durian seeds was 12,17 %. The composition of fatty acid containing in fatty oil was unsaturated fatty acid: oleic acid (14,95%) and linoleic acid (12,46%), and saturated fatty acid which is consist of stearic acid (45,84%) and palmitic acid, ( 26,75 %), relatively to pure stearic acid (E.Merck, pro analysis).Key Word: Durio zibethinus Murr, durian seed, fatty acids, identification